Amplification analysis at Nador city and surrounding area (NE of Morocco). (December 2022) - Chaaraoui, Aboubakr; Chourak, Mimoun; Hamdache, Mohamed; Peláez, José Antonio; Henares, Jesús
Abstract: This study presents a ground response assessment performed at Nador city (Morocco) and surrounding areas. We carried out the one-dimensional equivalent linear approach using the known geotechnical parameters to derive amplification analysis at studied sites, using the shear wave velocity (VS(30) ) derived from boreholes. Seismic hazard assessment is performed using two gridded seismicity models and four ground motions attenuation equations, in order to address the epistemic uncertainty in a logic-tree framework. Seismic hazard maps depicting the mean estimated hazard values and including the uncertainty are presented in terms of spectral acceleration at 0.0, 0.1 and 0.2 s, with 10% and 5% probabilities of exceedance in 50 years, and for B, B/C and C soil conditions, as defined by the National Earthquake Hazards Reduction Program classification and for local site conditions as well. Typical values of Peak Ground Acceleration (PGA) equal to 0.18 g ± 0.03 and 0.26 g ± 0.05 are obtained at the Nador city for 475 and 975 return period respectively and for B/C soil conditions. The deaggregation analysis for both returns periods (475 and 975 years) in terms of magnitude-distance (named 2D deaggregation) and in azimuth (longitude and latitude named 3D deaggregation) allows us to derive the contribution of the different couple of magnitude-distance ( M, D ) and the different sources, the controlling earthquake are also determined at the five considered cities, for both return periods. From the site-specific seismic hazard analysis performed at five main cities located in the studied area, the seismic hazard curves and the uniform hazard spectra (UHS) are obtained with their uncertainties for the considered return periods and soil conditions, as well as the design spectra proposed by Malhotra (2005). Real accelerogram time-history is used to generate compatible acceleration time-history with the design spectra proposed by Malhotra (2005) and the EC-8 type 2 (Eurocode 8.2004), for both return periods and for B/C soil conditions. The lower root mean square error value (RMSE) is archived by using the Malhotra design spectra for the considered return periods. The results display a clear amplification in silty and clayey soils, greater than in silt-gravely soils, as well as no significant amplification in volcanic soils. Moreover, the resulting fundamental frequency is in the range of 1.4–2.8 Hz, and the maximum amplification factor observed in Nador is about 3.5. These values are consistent with the results derived from ambient noise, seismic records using HVSR technique and with the values given by Moroccan Seismic Code in the 2000 and 2011 regulations. Highlights: Amplification analysis is performed at Nador city and surrounding area, based on the one-dimensional equivalent linear approach using given geotechnical parameters. We performed a probabilistic seismic hazard assessment for the region, in terms of peak ground acceleration (PGA) and spectral acceleration (SA) for different oscillation periods and for two return periods. Response spectra analysis is carried out from the artificial acceleration, dynamics soil parameters and site amplification has been evaluated for each soil type. The design spectra is carried out using the Malhotra procedure (Malhotra, 2005) and compared to the design spectra type II proposed by the EC 8.